Zoonotic tuberculosis knowledge and practices among cattle handlers in selected districts of Bangladesh. - Sk Shaheenur Islam; Tanzida Begum Rumi; S M Lutful Kabir; A K M Anisur Rahman; Md Mahmudul Hasan Faisal; Robiul Islam; Adri G M van der Zanden; Michael P Ward; Allen G Ross; Zeaur Rahim (Public Library of Science (PLoS), 2021)
We assessed zoonotic tuberculosis (zTB) knowledge and prevention and control practices of 404 cattle handlers via a survey in three dairy-intensive districts of Bangladesh. Most respondents were aged 30-49 (52%) and male (95%). Almost all (99%) recognized the important public health burden of tuberculosis in Bangladesh, however, most (58%) had inadequate knowledge about zTB transmission to humans. Inappropriate practices such as: not using protective equipment (98%); smoking, drinking or eating food whilst working with cattle (69%); and sharing the same premises with animals (83%) were identified. Cattle handlers educated at secondary or higher levels were 2.82- (95% CI: 1.59-5.10) and 5.15 times (95% CI: 1.74-15.20) more likely to have adequate knowledge of control and prevention activities compared to those with no formal education. Those who had reared animals for 1-5 years were 2.67 times (95% CI: 1.44-4.91) more likely to have adequate knowledge, compared to those who reared animals for >15 years. Cattle handlers with a monthly incomes of 10,000-20,000 taka were significantly (Odds Ratio = 0.36, 95% CI: 0.14-0.92) less likely to have adequate knowledge compared to those with monthly incomes <10,000 taka. Cattle handlers with high school or higher education were 6.98 times (95% CI: 2.47-19.71) more likely to use appropriate zTB control and prevention practices compared to those without formal education. Those who had reared animals for 1-5 years, 6-10 years and 11-15 years were 2.72- (95% CI: 1.42-5.24), 2.49- (95% CI: 1.29-4.77) and 2.86 times (95% CI: 1.13-7.23) more likely to apply appropriate practices compared to those who reared animals for >15 years. Overall, education, duration of cattle rearing and monthly income predicted zTB knowledge and practices. There is an urgent need to educate those at high-risk of zTB transmission on issues including the handling of infected animals, and general hygiene. A One Health approach, to support the Sustainable Development Goals and the End TB strategy, appears to be the way forward.